Does stigmatization wear down resilience? A longitudinal study among children affected by parental HIV. (July 2016) - Chi, Peilian; Li, Xiaoming; Du, Hongfei; Tam, Cheuk Chi; Zhao, Junfeng; Zhao, Guoxiang
Abstract: Social stigma has deleterious effects on psychological well-being. Emerging empirical evidences suggest that resilience is an adaptive mindset that generally enables people to survive and thrive in adversity. The current study used a three-wave longitudinal data to examine the potential bidirectional association between perceived stigmatization and resilience. Children of parents living with HIV (n = 195) were assessed at the baseline and followed up for 12 months with 6-month intervals. Cross-lagged panel analyses were performed in the study. The findings showed that the autoregressive effects were stable for perceived stigmatization and resilience, suggesting stable individual differences over time. The cross-lagged effects indicated that perceived stigmatization negatively predicted the level of resilience. However, resilience did not predict perceived stigmatization during the study time. The study suggests a robust longitudinal effect of perceived stigmatization on resilience. The potential bidirectional association between perceived stigmatization and resilience should be examined in the future studies. Highlights: A crossed-lagged model of perceived stigmatization and resilience is proposed. Perceived stigmatization negatively predicts the level of resilience over time. Resilience does not predict perceived stigmatization during the study time.